Gay Marriage in the New South: What's New About It? - Laurel Holland (Journal of Public and Professional Sociology)
In this special edition contributors were asked to explore the “New South.” In the call for papers, the editors noted that the South “has become the most vibrant part of the nation.” But they also recognize that the South still has its challenges based on a history of conflict and asked that authors consider areas where there is still work to be done. In this work I explore marriage equality and argue that while the Supreme Court of the United States recently ruled in a 5-4 decision that that the 14th Amendment requires states to marry same-sex couples and to recognize out-of-state same-sex marriages, there will continue to be unique challenges for these couples in the South. I argue that same-sex couples in the South will face significant cultural hurdles when compared to their heterosexual counterparts. I base my argument on the socio-historical conflict encountered by other minority groups in the South, especially, inter-racial couples, who faced particular challenges even after 1967 when the Supreme Court declared anti-miscegenation laws to be unconstitutional.